Identifying predictors of on-table adaptation for pancreas stereotactic body radiotherapy (SBRT). (May 2023) - Wu, Trudy C.; Yoon, Stephanie M.; Cao, Minsong; Raldow, Ann C.; Xiang, Michael
Highlights: A prescription dose >40 Gy in MRI-guided pancreas stereotactic body radiation therapy was associated with increased use of on-table adaptation. Clinical variables such as BMI, tumor location, technical resectability status and presence of vessel involvement are not reliable predictors of on-table adaptation. Dosimetric variables such as the gross tumor volume (GTV) size, planning target volume (PTV) size, minimum dose delivered to 95% (D95) of the GTV and PTV, GTV minimum, PTV minimum, conformity index, heterogeneity index, gradient index, and dosimetric parameters to organs at risk (OARs) (the absolute volume of an OAR receiving 20–35 Gy and dose maximum) are not reliable predictors of on-table adaptation. These findings emphasize the influential magnitude of stochastic day-to-day variations in patient anatomy, which can trigger on-table adaptation for a majority of fractions. On-table adaptive technology should be considered when delivering ablative doses to the pancreas. Abstract: Purpose: To identify any clinical or dosimetric parameters that predict which individuals may benefit from on-table adaptation during pancreas stereotactic body radiotherapy (SBRT) with MRI-guided radiotherapy. Methods and materials: This was a retrospective study of patients undergoing MRI-guided SBRT from 2016 to 2022. Pre-treatment clinical variables and dosimetric parameters on the patient's simulation scan were recorded for each SBRT course, and their ability to predict for on-table adaptation was analyzed using ordinal logistic regression. The outcome measure was number of fractions adapted. Results: Sixty-three SBRT courses consisting of 315 fractions were analyzed. Median prescription dose was 40 Gy in five fractions (range, 33–50 Gy); 52% and 48% of courses were prescribed ≤40 Gy and >40 Gy, respectively. The median minimum dose delivered to 95% (D95) of the gross tumor volume (GTV) and planning target volume (PTV) was 40.1 Gy and 37.0 Gy, respectively. Median number of fractions adapted per course was three, with 58% (183 out of 315) total fractions adapted. On univariable analysis, the prescription dose (>40 Gy vs ≤40 Gy), GTV volume, stomach V20 and V25, duodenum V20 and dose maximum, large bowel V33 and V35, GTV dose minimum, PTV dose minimum, and gradient index were significant determinants for adaptation (all p < 0.05). On multivariable analysis, only the prescription dose was significant (adjusted odds ratio 19.7, p = 0.005), but did not remain significant after multiple test correction (p = 0.08). Conclusions: The likelihood of needing on-table adaptation could not be reliably predicted a priori using pre-treatment clinical characteristics, dosimetry to nearby organs at risk, or other dosimetric parameters based on the patient's anatomy at the time of simulation, suggesting the critical importance of day-to-day variations in anatomy and increasing access to adaptive technology for pancreas SBRT. A higher (ablative) prescription dose was associated with increased use of adaptation.